Machining of advanced composite - Rafizuan, Ramli (2008)
In the laser drilling process, the quality of the drilled hole is the main task. A method of recognizing the effect on the quality of the laser drilled hole, by a few main process parameters needs to be developed, which seeks to improve the quality and explain the influence of each parameter. Twelve different holes have been drilled on two similar glass fiber composites with different laser power and pulse duration. Every hole then analyzed under optical microscope to inspect any comparable properties that can represent the quality of drilled holes itself. Preliminary result shown a significant different between comparable properties such as edge profile, burn mark diameter, heat affected zone and hole size prior to the increasing degree of parameters studied. The properties then evaluated by assigning a rating number from 1 to 10 to every comparable properties featured. Rating scheme conducted was highly based on comparative method between all holes. Laser power was then recognized as a most significant parameter in the laser drilling process.